2022
DOI: 10.1073/pnas.2120694119
|View full text |Cite
|
Sign up to set email alerts
|

Poly-2-methyl-2-oxazoline–modified bioprosthetic heart valve leaflets have enhanced biocompatibility and resist structural degeneration

Abstract: Bioprosthetic heart valves (BHV) fabricated from glutaraldehyde-fixed heterograft tissue, such as bovine pericardium (BP), are widely used for treating heart valve disease, a group of disorders that affects millions. Structural valve degeneration (SVD) of BHV due to both calcification and the accumulation of advanced glycation end products (AGE) with associated serum proteins limits durability. We hypothesized that BP modified with poly-2-methyl-2-oxazoline (POZ) to inhibit protein entry would demonstrate redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…To date, PEtOx appears to be the most investigated poly(2-oxazoline) in terms of biomedical applications [ 7 , 10 , 14 , 15 , 16 , 27 ], and PEtOx based polymer-drug conjugates and hemostatic materials have also reached human clinical trials [ 28 , 29 , 30 , 31 ]. Nonetheless, PMeOx is an important runner-up, and is especially attractive to shield drug carriers and for antifouling coatings based on its hydrophilicity, which is higher than that of PEtOx and PEG [ 17 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. It was shown that more hydrophilic PMeOx exhibits better anti-fouling properties than both PEtOx with longer side chains and PEG [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and allows higher hydrophobic drug loading [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, PEtOx appears to be the most investigated poly(2-oxazoline) in terms of biomedical applications [ 7 , 10 , 14 , 15 , 16 , 27 ], and PEtOx based polymer-drug conjugates and hemostatic materials have also reached human clinical trials [ 28 , 29 , 30 , 31 ]. Nonetheless, PMeOx is an important runner-up, and is especially attractive to shield drug carriers and for antifouling coatings based on its hydrophilicity, which is higher than that of PEtOx and PEG [ 17 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. It was shown that more hydrophilic PMeOx exhibits better anti-fouling properties than both PEtOx with longer side chains and PEG [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and allows higher hydrophobic drug loading [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…While comparing particular therapeutically significant properties, thiolated silica nanoparticles functionalized with PMeOx were shown to be considerably more penetrating through mucosal tissue than particles functionalized with PEtOx or poly-(2-n-propyl-2-oxazoline)s [ 39 ]. Another recent study showed that modification of bovine pericardium-based bioprosthetic heart valves with PMeOx creates a biocompatible surface that demonstrated enhanced resistance to serum protein infiltration and glycation and better thromboresistance compared to the PEG-modified version [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(2-oxazoline)s, pseudopeptides having pendent amido groups, are synthesized via ring-opening polymerization of 2-oxazoline [37][38][39][40][41][42][43][44][45][46][47] and are known to show excellent biocompatibility. [48][49][50][51][52][53][54][55][56] We have already reported incorporation of poly(2-oxazoline)s into biosynthesized artificial extracellular matrix protein (CS5-ELF) consisting of a REDV sequence in the cell-binding domain and an elastin-like sequence. [57][58][59][60] The side chain introduction of poly(ethylene oxide), [59] poly(2-oxazoline)s, [58] and poly(NIPAM), [60] enabled us to control both the lower critical solution temperature (LCST) and cell detachment from a surface.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these findings, mechanisms of SVD remain under continued study. Several works have implicated the degeneration of the extracellular matrix (ECM) and fibrocalcific remodeling by dystrophic calcification as major contributors to the pathogenesis of SVD ( 9 , 13 20 ).…”
mentioning
confidence: 99%
“…Given the role of circulating protein infiltration in initiating and directing BHV leaflet degeneration, we formulated and characterized a BHV biomaterial modified with poly-2-methyl-2-oxazoline (POZ) ( 19 ) aimed at reducing protein absorption. POZ is a novel compound in a class of antifouling polymers that blocks protein infiltration and resists oxidative stress.…”
mentioning
confidence: 99%